2013
DOI: 10.1088/0957-0233/24/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the transfer function for optical surface topography measuring instruments—a review

Abstract: A significant number of areal surface topography measuring instruments, largely based on optical techniques, are commercially available. However, implementation of optical instrumentation into production is currently difficult due to the lack of understanding of the complex interaction between the light and the component surface. Studying the optical transfer function of the instrument can help address this issue. Here a review is given of techniques for the measurement of optical transfer functions. Starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 168 publications
(256 reference statements)
0
23
0
Order By: Relevance
“…Alternatively, there are schemes for measuring the impulse response directly. [12][13][14] In conclusion, we have demonstrated that PSI can be used to measure the radius of cylindrical nanowires with nominal radii of 25 nm and 50 nm to within 4% of their nominal value. This relies on calibration of the experimental optical phase measurements to the results of a theoretical wave-optic model of the imaging of the nanowire by the PSI, modified to account for geometric shadowing due to the nanowire.…”
mentioning
confidence: 61%
“…Alternatively, there are schemes for measuring the impulse response directly. [12][13][14] In conclusion, we have demonstrated that PSI can be used to measure the radius of cylindrical nanowires with nominal radii of 25 nm and 50 nm to within 4% of their nominal value. This relies on calibration of the experimental optical phase measurements to the results of a theoretical wave-optic model of the imaging of the nanowire by the PSI, modified to account for geometric shadowing due to the nanowire.…”
mentioning
confidence: 61%
“…In order to understand the errors associated with CSI and other optical instruments it is useful to determine their 3D transfer characteristics [11,12]. In a recent work, the process of scattering from the smooth interface between homogenous materials was considered, and it was shown that, with appropriate assumptions, CSI can be described by a 3D filtering operation [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the non-contact measurement of the surface profile, the phase shifting interferometry [6][7][8][9][10][11] requires multiple fringe patterns to reconstruct the surface profile of an object.…”
Section: Introductionmentioning
confidence: 99%